Academic Motivation: Gender, Domain and Grade Differences - Hakan, Karatas; Munire, Erden (ELSEVIER SCIENCE BV, 2014)
Academic motivation is a key determinant of academic performance and achievement. The purpose of this study was to determine undergraduates' academic motivation in terms of gender, domain and grade differences. The participants of the study consisted of 750 undergraduates studying in different departments. To determine the individual differences in undergraduates' academic motivation, data were collected using Academic Motivation Scale, originally developed by Vallerand et al. (1992) and Turkish bilingual equivalence, validity and reliability of which carried out by Karatas and Erden, (2011), was used. Analyses of t-test were conducted to determine the undergraduates' academic motivation in terms of their gender, domains and grades. The results revealed that significant differences were found in undergraduates' academic motivation according to gender, domain and grade. These findings and implications for educational researchers were discussed. (C) 2014 Published by Elsevier Ltd.
Keywords: Amotivation; intrinsic motivation; extrinsic motivation; SELF-DETERMINATION THEORY; FUTURE TIME PERSPECTIVE; 5 PERSONALITY-TRAITS; STUDENT MOTIVATION; ACHIEVEMENT; EDUCATION; ORIENTATIONS; VALUES; GOALS; Education & Educational Research